The quality of surimi made from Threadfin bream stored on ice for different periods - Yu, Swee Yean (Wiley, 1993)
Surimi gels prepared from Threadfin bream (Nemipterus tolu) stored on ice for up to 8 days showed no significant differences in protein, fat, and moisture contents, but the yield decreased significantly after 2 days. Protein losses increased, but not significantly. Gel strength (hardness) was still acceptable after 2 days on ice, but then declined rapidly to unacceptable by 4 days on ice. N. tolu should not be kept on ice for more than 2 days for production of surimi of acceptable quality.